2003
DOI: 10.2138/am-2003-0405
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Zn/Al hydrotalcite in smelter-impacted soils from northern France: Evidence from EXAFS spectroscopy and chemical extractions

Abstract: Zinc speciation was studied by EXAFS spectroscopy, m-SXRF elemental mapping, XRD, and chemical extraction methods in two smelter-impacted soils sampled near one of the largest Pb and Zn processing plants in Europe, which is located in northern France about 50 km south of Lille. The tilled and wooded soils chosen for study differ in Zn concentration (ª600 and 1400 mg/kg, respectively), soil pH (7.5 and 5.5, respectively), and organic matter content (1.5 and 6.4 wt% TOC, respectively). In both soils, the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
112
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 68 publications
15
112
3
Order By: Relevance
“…Juillot et al (19) found that 12% of Zn was CaCl 2 -exchangeable, and concluded from EXAFS and chemical extraction data that outer-sphere Zn was present in this soil. In this study, the comparison of Zn contained in the bulk soil before fractionation and the weighted sum of Zn in the size fractions shows that ~ 20% of Zn was leached during size fractionation (Table 1).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Juillot et al (19) found that 12% of Zn was CaCl 2 -exchangeable, and concluded from EXAFS and chemical extraction data that outer-sphere Zn was present in this soil. In this study, the comparison of Zn contained in the bulk soil before fractionation and the weighted sum of Zn in the size fractions shows that ~ 20% of Zn was leached during size fractionation (Table 1).…”
Section: Resultsmentioning
confidence: 73%
“…Outer-sphere and organic Zn species have been suggested to amount ~ 50-60% in an organic acidic soil (pH 5.5) (19), and otherwise are present in subordinate amount in soils dominated by mineral constituents. In these soils, a varieties of Zn-sorbed and Zn-substituted secondary species were identified, including phyllosilicates, iron oxyhydroxides, manganese oxides, lithiophorite, hydrotalcite and phosphate (8,16,18,19,22). On the basis of these results, Zn-organic complexes seem to prevail in highly organic soils at moderately acidic pH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the element of interest is present in several forms, their identification can be challenging because the EXAFS signal is the weighted sum of the individual spectra from the component species. To reduce the number of components or modify their proportions, physical and chemical treatments can be used to remove or concentrate certain species Isaure et al, 2002;Scheinost et al, 2002;Juillot et al, 2003). Alternatively, the size of the X-ray probe can be adapted to a particular scale dependent on the heterogeneity of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…readily be transported and suspended in water, while the biggest and heaviest ones settle in the basin. These spherical particles are typical of ash produced during metallurgic processes [54,55]. They result from the combustion, melting and volatilization of ore minerals and commonly consist of slag and matte droplets, graphite, and condensed particles, which are collected by filters.…”
Section: Nickel Bearing Phasesmentioning
confidence: 99%